Sintesis Senyawa Asetil Vanilat melalui Vanilin dan Peranannya Sebagai Komponen Senyawa Analgesik - Salman Salman; Elvira Julia Ariyanto; Shafira Intan Anggraini; Siti Nafisa; Welly Windari (Journal of Pharmaceutical and Sciences, 2023)
People in Indonesia are inseparable from pain such as pain. This pain disease is treated with analgesic drugs such as aspirin. Where in aspirin, the salicylate group is most widely used as an analgesic. Aspirin differs from other salicylic acid derivatives in that it has an acetyl group. It is this acetyl group that can inactivate cyclooxygenase, so this drug is called an NSAID. In the synthesis of acetyl vanillate from aspirin via vanillin, the aim is to obtain the synthesis of acetyl vanillic compounds. Vanillin oxidation was carried out using Tollens reagent (AgNO3). The results of the FTIR spectrum showed that there were differences in acetyl vanillic and vanillic acid compounds. Synthesis of acetyl vanillic is carried out by oxidizing vanillin to produce vanillic acid which is then carried out by acetylation of vanillic acid to form acetyl vanillic compounds. The resulting compounds were characterized using the FTIR spectrum and compared to their identification using HNMR. Identification using FTIR is better than HNMR because the carboxylic acid group appears compared to HNMR. HNMR is covered with a large peak of carboxylic groups in the proton environment.